Crimean-Congo hemorrhagic fever virus strains Hoti and Afghanistan cause viremia and mild clinical disease in cynomolgus monkeys. - Robert W Cross; Abhishek N Prasad; Viktoriya Borisevich; Joan B Geisbert; Krystle N Agans; Daniel J Deer; Karla A Fenton; Thomas W Geisbert (Public Library of Science (PLoS), 2020)
Background Development of vaccines and therapies against Crimean-Congo hemorrhagic fever virus (CCHFV) have been hindered by the lack of immunocompetent animal models. Recently, a lethal nonhuman primate model based on the CCHFV Hoti strain was reported. CCHFV Hoti caused severe disease in cynomolgus monkeys with 75% lethality when given by the intravenous (i.v.) route. Methodology/principal findings In a series of experiments, eleven cynomologus monkeys were exposed i.v. to CCHFV Hoti and four macaques were exposed i.v. to CCHFV Afghanistan. Despite transient viremia and changes in clinical pathology such as leukopenia and thrombocytopenia developing in all 15 animals, all macaques survived to the study endpoint without developing severe disease. Conclusions/significance We were unable to attribute differences in the results of our study versus the previous report to differences in the CCHFV Hoti stock, challenge dose, origin, or age of the macaques. The observed differences are most likely the result of the outbred nature of macaques and low animal numbers often used by necessity and for ethical considerations in BSL-4 studies. Nonetheless, while we were unable to achieve severe disease or lethality, the CCHFV Hoti and Afghanistan macaque models are useful for screening medical countermeasures using biomarkers including viremia and clinical pathology to assess efficacy.